Comparative analysis between abdominal aortic aneurysm and popliteal artery aneurysm - Marcos Vinícius Melo de Oliveira, MD, PhD; Alexandre Malta Brandão, MD, PhD; Gina Camillo Rocha Silvestre, BS; Alexandre Queiroz Silva, BS; Michele Alberto Marques, BS; Marcia Martins Reis, PhD; Maria de Lourdes Higuchi, MD, PhD; Erasmo Simão da Silva, MD, PhD (JVS - Vascular Science, 2025)
Objective: Infrarenal abdominal aortic aneurysm (AAA) and popliteal artery aneurysm (PAA) are localized arterial dilatations with distinct clinical outcomes. This study aimed to comprehensively compare these two types of aneurysms' biomechanical, histological, and immunohistochemical characteristics. Methods: This study included 180 patients with AAA and 18 with PAA. Medical history and imaging data were collected. Biomechanical testing assessed arterial wall mechanical strength and elasticity, and histological and immunohistochemical analyses examined tissue composition and inflammatory markers. Results: PAA wall fragments demonstrate higher failure strain energy (13.36 N/m2 vs 9.95 N/m2; P = .023), a measure of mechanical strength. Regarding immunohistochemical markers, AAA exhibited more B lymphocyte cells in the adventitia (CD20 1475.50 vs 320; P = .003) compared with PAA. Additionally, AAA demonstrated more adipogenic differentiation in the adventitia (PPARgamma 4854.50 vs 778; P = .009), whereas PAA showed more adipogenic differentiation in the intima (KLF5 283.50 vs 77.50; P = .039). Conclusions: PAA wall fragments demonstrate greater mechanical strength compared with AAA wall fragments. In contrast, AAA walls contain a greater number of B lymphocytes within the adventitia compared with PAA walls. Adipogenic differentiation is more pronounced in the adventitia of AAA than in PAA, whereas in PAA, it is more prominent in the intima compared with AAA. Clinical Relevance: The clinical significance of this study lies in its potential to enhance our understanding of the distinct pathophysiological mechanisms underlying abdominal aortic aneurysms, which is often associated with rupture, and popliteal artery aneurysms, which are more prone to thrombosis and distal embolization. By comprehensively comparing the biomechanical, histological, and immunohistochemical aspects of these two aneurysm types, the study aims to illuminate the factors contributing to their differing clinical presentations and outcomes.